The MAJORANA DEMONSTRATOR Neutrinoless Double-Beta Decay Experiment. (29th January 2014) - Abgrall, N.; Aguayo, E.; Avignone, F. T.; Barabash, A. S.; Bertrand, F. E.; Boswell, M.; Brudanin, V.; Busch, M.; Caldwell, A. S.; Chan, Y.-D.; Christofferson, C. D.; Combs, D. C.; et al.
Abstract : The Majorana Demonstrator will search for the neutrinoless double-beta ( β β 0 ν ) decay of the isotope 76 Ge with a mixed array of enriched and natural germanium detectors. The observation of this rare decay would indicate that the neutrino is its own antiparticle, demonstrate that lepton number is not conserved, and provide information on the absolute mass scale of the neutrino. The Demonstrator is being assembled at the 4850-foot level of the Sanford Underground Research Facility in Lead, South Dakota. The array will be situated in a low-background environment and surrounded by passive and active shielding. Here we describe the science goals of the Demonstrator and the details of its design.